MICRO FINANCING SCHEME BASED ON OPTIMIZATION OF NETWORK (MFS-ON): APROPOSED IMPROVEMENT ON CURRENT PRACTICES - Soenartomo Soepomo; Moch. Doddy Ariefianto (Jurnal Keuangan dan Perbankan, 2011)
One important method in reducing poverty was through finance.The poor were lack of qualification andcapacity to borrow from formal financial sector. Therefore they should resort their financing needs to informalsources albeit very high cost implication.This dependency in turn would disrupt their productive capacitysincethe interest was very high. We focus on special segment of theproductive poor. We reviewed various financingscheme that widely practiced both domestically and globally. We perceived that existing schemes were inadequatefrom several perspectives: (1) partial nature, (2) substandard business practices, (3) lack of cooperationand (4) limited coverage. We proposed an alternative financing scheme.The spirit of the approach emphasizedthe critical role of self-sufficiency of Microfinance Institution (MFI). Through self sufficiency, MFI coulddevelop a healthy business with reasonable rate of return. In addition to self sufficiency, first, the proposal alsoincluded financing from private sector through mobilization of Corporate Social Responsibility (CSR) funds.The funding sources became broad and economics scale could be achieved. Second, the proposal improved risksharing mechanism by introducing the regional government banks as well as insurers. Third, the proposalmade the distribution channel optimum by involvement of society elements